2008
DOI: 10.2147/opth.s3881
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety, and improved tolerability of travoprost BAK-free ophthalmic solution compared with prior prostaglandin therapy

Abstract: Purpose: To evaluate the effi cacy, safety and tolerability of changing to travoprost BAK-free from prior prostaglandin therapy in patients with primary open-angle glaucoma or ocular hypertension. Design: Prospective, multi-center, historical control study. Methods: Patients treated with latanoprost or bimatoprost who needed alternative therapy due to tolerability issues were enrolled. Patients were surveyed using the Ocular Surface Disease Index (OSDI) to evaluate OSD symptoms prior to changing to travoprost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
0
10
1
1
Order By: Relevance
“…Different preservativefree PGAs are currently available that are no less effective in reducing IOP than their preserved counterparts [26e28]. Furthermore, switching studies revealed that changing from preserved to preservative-free medications significantly improved signs and symptoms related to OSDs [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Different preservativefree PGAs are currently available that are no less effective in reducing IOP than their preserved counterparts [26e28]. Furthermore, switching studies revealed that changing from preserved to preservative-free medications significantly improved signs and symptoms related to OSDs [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous large multicenter clinical trial of patients with glaucoma who had been previously treated with either latanoprost 0.005% or bimatoprost 0.03%, and who needed alternative therapy due to tolerability issues, a switch to BAK-free travoprost 0.004% resulted in improvement in OSD symptoms that were both clinically and statistically significant, and maintained equal or better control of IOP. 14 However, that study was not conducted in a parallel, randomized, masked fashion. The objective of this current multicenter, double-masked, randomized, controlled study was to quantify changes in symptoms of OSD after randomizing patients with open-angle glaucoma or ocular hypertension who were previously treated with latanoprost 0.005% preserved by 0.02% BAK (Xalatan ® ophthalmic solution; Pfizer Inc., NY) either to remain on BAK-preserved latanoprost 0.005% or to change to BAK-free travoprost 0.004% (Travatan Z ® ophthalmic solution; Alcon Laboratories, Inc., Fort Worth, TX).…”
Section: Introductionmentioning
confidence: 99%
“…Surface inflammation is a hallmark of OSD and topical treatment toxicity. 33,34 Bulbar redness had a significant improvement after OSD treatment in both eyes. Although several antiglaucoma medications lead to conjunctival hyperemia, 29,35,36 the significant reduction in bulbar redness occurred despite the maintenance of all glaucoma eyedrops previously in use.…”
Section: Discussionmentioning
confidence: 94%
“…38,39 Henry et al have observed statistically significant IOP reduction in glaucoma patients who switched from BAK-preserved prostaglandin to preservativefree travoprost. 34 In a similar study, but with a very small sample (n=4), Batra et al suggested that severe OSD could exacerbate glaucoma due to inflammation and scarring of the trabecular meshwork and demonstrated that an intensive OSD treatment including preservative-free lubricants, preservativefree antiglaucoma medication and oral doxycycline improved IOP control. 22 Their study was a retrospective review of the files of four patients with uncontrolled primary open angle glaucoma.…”
Section: Discussionmentioning
confidence: 96%